Kombinasi Metode Rank Sum dan Grey Relational Analysis dalam Pemilihan Pelanggan Terbaik - Sriyasa, I Wayan (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
Selecting the best customers is an important process in marketing and customer relationship management (CRM) strategies that aim to identify the customers who contribute the most to the success of the business. The main problem in selecting the best customer lies in the difficulty in objectively assessing and comparing customer performance, given the diversity of characteristics of each customer. The combination of rank sum and GRA methods is an approach that combines two powerful techniques in multi-attribute decision-making to evaluate and select the best alternatives. This approach aims to overcome the limitations of each method when used separately, and take advantage of the advantages of both methods in producing more objective and accurate decisions. The results of the alternative ranking show that Customer C is ranked first with a value of 0.2, followed by Customer A (0.1865) and Customer G (0.1864). Meanwhile, customers with the lowest GHG values, such as Customer H (0.0167), are in last position because their performance is furthest from ideal conditions. These results help visualize the ranking order based on the performance of each alternative, making it easier to make decisions in choosing the best customers. This research contributes to generating objective and transparent decisions, as well as helping companies identify potential customers based on criteria such as loyalty, revenue contribution, or long-term potential.